Effect of box height on box jump performance in elite female handball players - Koefoed, N.; Dam, S.; Kersting, U. G. (The Journal of Strength and Conditioning Research, 2022)
This study aimed at investigating whether a link exists between performance in a countermovement jump and the height of the box an athlete could successfully jump onto. Furthermore, it was investigated whether the height of the box influences the takeoff. Ten, elite, female team, handball players were recruited for the study (age: 20.9 ± 3.2 years; height: 174.7 ± 7.6 cm; mass: 73.8 ± 6.7 kg). Subjects performed 3 maximal countermovement jumps. Subsequently, subjects jumped onto boxes of increasing height until they could no longer successfully jump onto the box. Subjects then performed 3 box jumps with maximal intention to boxes corresponding to 70% of their maximal center of mass displacement (LOW) and 90% of their maximal achieved box height (HIGH). Finally, subjects completed another 3 maximal countermovement jumps. There was no relationship between the maximal center of mass displacement in countermovement jumps and the maximal achievable box jump height (r2 = 0.35; p = 0.071). Between jumps to LOW and HIGH boxes, there were no differences in the chosen variables, peak force (-156 ± 390 N; p = 0.239), peak power (25 ± 236 W; p = 0.747), peak center of mass displacement (0.003 ± 0.039 m; p = 0.840), peak rate of force development (-3.055 ± 6264 N/s; p = 0.157), and concentric time to takeoff (0.005 ± 0.044 seconds; p = 0.721). Because no differences could be found, the added risk of failure leading to injury and the limited possibilities of improving specific landing technique with low impact when jumping to high boxes in training cannot be justified.